Microfluidic Platform for Seawater Desalination by Coulometric Removal of Chloride Ions through Printed Ag Electrodes. Issue 12 (13th September 2017) - Fighera, M.; van der Wal, P. D.; Shea, H.
Abstract : This paper reports on the electrochemical characterization and comparison of printable silver inks for the fabrication of planar electrodes to integrate in a microfluidic platform for in situ desalination of seawater prior to detection of nutrients in marine environment. Screen printing and inkjet printing were investigated to overcome limitations of more conventional deposition techniques. The screen printed ink DuPont 5064H was chosen for the fabrication of the desalination platform as it displayed the best properties in terms of oxidation ability (15.5 mC/mm 2 ) and absence of sample contamination. The platform was tested at different oxidation conditions; the optimum potential for desalination was found to be +0.9 V. The device desalination performance was then evaluated through conductivity measurements of the treated sample and a proof-of-concept was achieved: for a potential of +0.9 V, conductivity (hence concentration) could be lowered from an initial value of 42.13 mS (0.6 M) to 20.36 mS (0.206 M), 17.37 mS (0.157 M) and 6.38 mS (0.0516 M) for oxidation times of 120 s, 240 s and 360 s, respectively. The operating conditions allowed the regeneration of the silver electrode and the possibility to deploy it for six to ten cycles before depletion of the silver working electrode.